Livelihood Changes of Construction Migrant Workers in the New Capital City of Indonesia - Marella, Fairuza Rakhsi; Cherlys, Cherlys; Nurjannah, Shofiya; Meiana, Aisyah Ratna; Pratiwi SP, Auliya Widyaningrum; Aditya, Arta; Prasetyo, Budi; Widyatna, Finna Anindya; Putra, Galih Wijaya Surya; Wisnugroho, Benedictus Haryo; Salma, Khansa Hafshah; Prakoso, Gunawan; Zulkarnain, Muhammad Syahrian; Rahadini, Keisha Devana; Ramadhisa, Nasywa; Wulandari, Laila Amalia; Sari SPD, Widi; Atallah, Muhammad Haikal Giffari; Rahmadani, Zenobia; Permana, Radjani Shafa; Normalita, Reyna (Sekolah Tinggi Pertanahan Nasional, 2025)
The relocation of Indonesia’s new capital city (IKN) to Sepaku District, East Kalimantan, has triggered a significant influx of construction migrant workers, creating complex livelihood dynamics. The central issue is how this labor migration not only generates opportunities for improved welfare but also introduces new vulnerabilities across social, economic, and environmental dimensions. This study aims to analyze the livelihood transformations of migrant workers using the Sustainable Livelihoods Framework (SLF), which encompasses five core capitals. A qualitative descriptive approach was employed, combining in-depth interviews with migrant workers and local communities with supporting document analysis. Informants were selected through snowball and accidental sampling, and data were thematically analyzed to identify positive and negative impacts as well as cross-capital implications. Findings indicate that IKN development enhances human capital through skill acquisition and opens new economic opportunities (financial capital). However, vulnerabilities persist due to precarious employment, weak social protection, limited access to basic infrastructure, and environmental degradation affecting worker health. Thus, the success of IKN depends on policies that balance infrastructure development with the protection and strengthening of migrant workers’ livelihood assets as key actors in national transformation.